Wolf Hollow : a novel - Wolk, Lauren, 1956- (New York, NY : Dutton Children's Books, an imprint of Penguin Random House LLC, 2016)
"Twelve-year-old Annabelle must learn to stand up for what's right in the face of a manipulative and violent new bully who targets people Annabelle cares about, including a homeless World War I veteran"--
Keywords: Conduct of life -- Fiction; Bullying -- Fiction; Homeless persons -- Fiction; Veterans -- Fiction; Family life -- Pennsylvania -- Fiction; JUVENILE FICTION / Historical / United States / 20th Century; JUVENILE FICTION / Social Issues / Bullying; JUVENILE FICTION / Lifestyles / Country Life; Pennsylvania -- History -- 20th century -- Fiction